Pengaruh Profitabilitas dan Pertumbuhan Penjualan Terhadap Harga Saham dengan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Sub Sektor Pariwisata, Restoran, dan Hotel yang Terdaftar di Bursa Efek Indonesia - Oktarianti, Rz Nur; Djazuli, Abid; Choiriyah, choriyah (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
This study aims to determine and analyze the effect of profitability and sales growth on stock price with capital structure as an intervening variable at tourism, restaurant, and hotel sub-sector companies listed on the Indonesia stock exchange. The research design used associative methods. The sampling technique was purposive sampling. The total samples were 20 companies. The technique of collecting data was documentation. The techniques used were the classical assumption model test, path analysis, and t-test. The results of this study indicate that Profitability has a significant influence on capital structure. Sales growth has a significant influence on capital structure. Profitability has a significant influence on stock price. Sales growth has a significant influence on stock price. Capital structure has a significant influence on stock price. There is no influence of capital structure mediation on the indirect influence of profitability on stock price. There is no influence of capital structure mediation on the indirect influence of Sales growth on stock price.